Digestible Threonine Requirements for Maintenance in the Starting Turkey - Sun, S.; Brown, J.; Firman, J.; Kamyab, A.; McGill, E. (International Journal of Poultry Science, 2007)
The objective of these studies was to determine the digestible threonine requirement for maintenance in turkeys during the starter period. Amino acid requirement data can be determined in multiple fashions. One method for determining amino acid requirements is through modeling. A portion of the data required for a comprehensive model is the maintenance requirement. Two studies were conducted to determine the maintenance requirement for threonine during the starter period for turkeys. Day-old poults (192 birds) were randomly assigned to pens to provide for six replications of eight treatments in each trial and a low protein diet was formulated so that different levels of threonine could be fed to young turkeys. The maintenance requirements of threonine were 25.94 and 29.51 mg/bird/day in experiment 1 and experiment 2, respectively. This information, coupled with the amino acid requirements for growth, will allow for the construction of an effective model to predict amino acid requirements over a wide range of environment and physiological conditions.